STUDY OF MORSE RATE OF RESIDENTS OF THE CITY OF BUKHARA DEPENDING ON THE ACTIVITY OF THE EARTH’S MAGNETIC FIELD. - Niyazkhonova Bashorat Eshmamatovna; Nurilloeva Feruza Amrillo kizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article studied the influence of magnetic storms and disturbed geomagnetic conditions on the health of the inhabitants of the city of Bukhara for three months and developed recommendations in order to reduce the harmful effects of these days on humans.